Candida utilis ATCC 9950 Cell Walls and β(1,3)/(1,6)-Glucan Preparations Produced Using Agro-Waste as a Mycotoxins Trap - Anna Bzducha-Wróbel; Marcin Bryła; Iwona Gientka; Stanisław Błażejak; Monika Janowicz (Toxins, 2019)
Mycotoxins are harmful contaminants of food and feed worldwide. Feed additives with the abilities to trap mycotoxins are considered substances which regulate toxin transfer from feed to tissue, reducing its absorption in animal digestive tract. Market analysis emphasizes growing interest of feed producers in mycotoxins binders obtained from yeast biomass. The aim of the study was to prescreen cell walls (CW) and β(1,3)/(1,6)-glucan (β-G) preparations isolated from Candida utilis ATCC 9950 cultivated on waste potato juice water with glycerol as adsorbents for aflatoxin B1 (AFB1), zearalenone (ZEN), ochratoxin A (OTA), deoxynivalenol (DON), nivalenol (NIV), T-2 toxin (T-2) and fumonisin B1 (FB1). The adsorption was studied in single concentration tests at pH 3.0 and 6.0 in the presence of 1% of the adsorbent and 500 ng/mL of individual toxin. Evaluated CW and β-G preparations had the potential to bind ZEN, OTA and AFB1 rather than DON, NIV, T-2 toxin and FB1. The highest percentage of adsorption (about 83%), adsorption capacity (approx. 41 µg/ g preparation) and distribution coefficient (458.7mL/g) was found for zearalenone when CW preparation was used under acidic conditions. Higher protein content in CW and smaller particles sizes of the formulation could influence more efficient binding of ZEN, OTA, DON and T-2 toxin at appropriate pH compared to purified β-G. Obtained results show the possibility to transform the waste potato juice water into valuable Candida utilis ATCC 9950 preparation with mycotoxins adsorption properties. Further research is important to improve the binding capacity of studied preparations by increasing the active surface of adsorption.